Characterization of a chiastolite-type andalusite: structure and physicochemical properties related to mullite transformation. (1st July 2022) - Mouiya, Mossaab; Arib, Abdelhak; Taha, Yassine; Tamraoui, Youssef; Hakkou, Rachid; Alami, Jones; Huger, Marc; Tessier-Doyen, Nicolas
Abstract: Chiastolite-type andalusite, whose genesis occurred in the currently unexploited deposit of Sidi Bou Othman (Morocco), has been extensively characterized. The phase composition, microstructure, thermal behavior, sinterability, and evolution of the crystallographic structure associated with the transformation of andalusite to mullite were accurately analyzed. Parallelepiped-shaped crystal grains exhibited off-white X crosses, typical of the chiastolite group. The chemical composition is closely dependent on the crystal size and proportion of alumina. The crystal structure was successfully refined using XRD, and chemical analysis was performed for different crystal sizes up to 30 mm. Powder compacts were prepared from these chiastolites for further characterization after various thermal treatments. According to the Rietveld refinement analysis, the mullization ranges from 1200 to about 1500 °C, and crystallographic parameters have been compared with other andalusites reported in literature. In agreement with this phase transformation, variations related to different material properties such as thermal expansion, pore volume fraction, and mechanical strength were evaluated. These results highlight the potential for further exploitation of the Sidi Bou Othman deposit to produce refractory materials.